Structural fiscal balance Costa Rica 1998 – 2014 - Rojas, Daniel (2017)
This article presents a structural fiscal balance for the Costa Rican economy. The structural balance is an ex-post indicator of fiscal policy performance which attempts to contribute to the development of a fiscal rule. In order to derive this indicator the IMF’s general methodology was applied to data from the Costa Rican Ministry of Finance. The elasticities of tax revenues and current expenditure to national output were estimated by means of a simple OLS model while potential output was estimated by means of the Hodrick-Prescott. The article’s main conclusion is that the structural fiscal balance moves in the same direction as that of the output gap.